IMPLEMENTATION OF THE PROCESS FOR RESOLVING VIOLATIONS OF LOCAL REGULATIONS ON WASTE MANAGEMENT IN YOGYAKARTA CITY - Hidayatulloh, Bagus Anwar (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims to evaluate the implementation process for resolving violations related to the Local Regulation on Waste Management in Yogyakarta City. With the increasing population growth and urbanization, waste management in this city has become a complex challenge. Despite regulations being in place, violations of waste management rules still occur. This study will investigate the stages of law enforcement against violations, particularly the use of light criminal sanctions (tipiring) applied by the Yogyakarta City Government through the Public Order Police Unit (Satpol PP). The background of the research is based on the fact that the success of a regulation lies not only in its creation but also in its implementation in daily practice. The research will delve into the process of resolving violations to evaluate its effectiveness, identify obstacles, and provide recommendations for improvements to achieve sustainable waste management in Yogyakarta City. This research utilizes a normative juridical method and seeks to contribute to local governments, related institutions, and the community in improving waste management systems more effectively in accordance with regulations. The findings indicate that the handling of waste violations in Yogyakarta City can be done both outside and within the judicial system.